Holocaust Angst : the Federal Republic of Germany and American Holocaust memory since the 1970s - Eder, Jacob S. (Oxford University Press, 2016)
Holocaustomania: West German diplomats and American Holocaust memorial culture in the late 1970s -- A "Holocaust syndrome"? Relations between the Federal Republic and American Jewish organizations in the 1980s -- Confronting the "anti-German museum": West Germany and the United States Holocaust Memorial Museum, 1979-1993 -- Politicians, professors, and the politics of German history in the American academy from the 1970s to 1990 -- The transformation of Holocaust memory in unified Germany, 1990-1998 -- Holocaust angst and the universalization of the Holocaust